An application of physiological anthropometry: the determination of leg subcutaneous fat, muscle and bone widths and volumes in young male and female adults - Peter R.M. Jones (1970)
An application of physiological anthropometry: the determination of leg subcutaneous fat, muscle and bone widths and volumes in young male and female adults